Catholic schools in Scotland and divisiveness - McKinney, Stephen J. (Journal of beliefs and values, 2008)
Faith schools and divisiveness is one of the key issues in the faith school debates in both England and Wales and Scotland. In Scotland the faith school debate is focused on Catholic schools. This paper, based on a review of relevant literature and the findings of a series of expert interviews, argues that the complexity of this issue of the divisiveness of faith schools in Scotland can be best understood through the adoption of six categories of divisiveness. These six categories illuminate the debate and raise important questions about the nature and position of Catholic schools in contemporary Scottish society.